Model Ekologi Sosial Problem Solving Anak Korban COVID 19 - Susi Fatma Yuwita; Tyas Retno Wulan; Sulyana Dadan (Journal on Education, 2024)
This article explains the social ecological model of problem solving for child victims of COVID 19 as an effort to handle a sensitive and comprehensive approach to help them overcome the various social problems they face. Action or intervention plans must be tailored to existing needs and resources. The aim of this research is to examine the social ecological model of problem solving for child victims of COVID 19. The theory used is the sociological theory of Tancolt Parsons Adaptation, Goal Attainments, Integration and Latency. The research method used is qualitative with a literature study approach. The research results found that the social system has an important role as a comprehensive multilevel analysis and the central concept is collaboration and involvement of related parties in handling child victims of COVID 19. The conclusion of this research is that the social ecological model of problem solving for child victims of COVID 19 requires several comprehensive approaches that where social handling does not only focus on the individual himself but involves several aspects, including family, group, community, surrounding environment or society from various stakeholders by identifying existing problems, making action/intervention plans, implementing actions/interventions and necessary there is also an evaluation. This research can be useful in the field of sociology of community empowerment. This research can provide benefits to readers regarding the social ecological model of problem solving for children who are victims of COVID 19